Pengaruh Keberdayaan Masyarakat Dalam Pemanfaatan Potensi Lokal Terhadap Peningkatan Kesejahteraan Anggota Kelompok Wanita Tani - Indri Dwi Ramadani; Wiwin Herwina; Bayu Adi Laksono (Lifelong Education Journal, 2022)
Indonesia is a country where the majority of the work is as a farmer. Agricultural problems in Ciamis Regency, especially Lumbung Village, such as low yields and lack of community participation must be addressed by various parties, especially the Women Farmers Group (KWT) as one of the implementers of agriculture in managing agricultural land. Women Farmer Groups (KWT) must be efficient, capable, and independent in order to improve the economy of the community and family. The purpose of this study was to determine the effect of community empowerment in utilizing local potential to improve the welfare of members of the Women Farmers Group. The method used in this research is correlational quantitative method with data collection techniques through observation, questionnaires, and documentation. The analysis technique used is classical assumption test and simple linear regression test using SPSS. The population used is all members of the Women Farmers Group (KWT) as many as 60 people. The sample was taken using the Slovin formula and the technique used was the Cluster Random Sampling technique which resulted in a sample of 37 members of the Women Farmers Group (KWT). The results of research that have been carried out by testing the hypothesis that there is an influence of community empowerment in the utilization of local potential on increasing the welfare of members of the Women Farmers Group (KWT) is 12%. The multiple correlation value (R) of 0.355 indicates a weak relationship between the community empowerment variable and the community welfare variable. The conclusion of this study is that there is a positive and significant influence between community empowerment in the utilization of local potential to increase the welfare of members of the Women Farmers Group (KWT).